EVALUASI PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DI DESA MEKAR SARI KECAMATAN SERAWAI KABUPATEN SINTANG - DEWI KURNIATI, NIKEN PUSPITA RINI, EVA DOLOROSA, (Jurnal Social Economic of Agriculture, 2019)
Food Security is the condition of the fulfillment of food for every household with the availability of good enough food in quantity and quality safe, evenly and affordably. The existence of the land yanag increasingly narrower the area of agricultural land diminishing, so that the management of agricultural resources that can provide benefits and contribute income households farmers is by empowering the field of nesting. This study aims to determine the type of crops cultivated, how much production and contribution or contribution of production from farming business on the income of farm households, malalui direct observation. The results showed that the KRPL program is a set of several households and utilized the keralan for five vegetable commodities namely kale, mustard greens, spinach, chilli and tomato. Household management and farming production in the Sustainable Food House (KRPL) program in Mekar Sari Village is quite good to be seen from the additional income of farmers of the KRPL program for family welfare and contributes 14,87%  to total household income. Keywords :  Food Security, production, contribution, yard farming